Texts of political leaders’ speeches: discourse analysis - Aйтмухaмбет, С.; Aхметбековa A.К., А К. (Journal of Oriental Studies, 2017)
The article considers speeches of the Iranian leaders as part of a political discourse. Types of political texts, such as «aggressive», «scandalous», «vigorous» expressionally and emotionally transfer a concept of the text and are unit of the discourse analysis.